Kompetensi Pendamping Simantri dalam Pembuatan Biourine pada Kelompok Simantri di Kabupaten Tabanan - ANDITA, I MADE PRADNYA; PUTRA, I GEDE SETIAWAN ADI; ANGGRENI, I G A A LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Competency Of Simantri Companion In Making Biourine In The Simantri Group In Tabanan Regency. Integrated farming system (Simantri) is one of the superior programs of the Bali Provincial Government to increase the role of the agricultural sector and support the making of organic fertilizer. Organic fertilizers are in solid and liquid forms. extension agents play an important role in increasing the competency of farmers in making liquid organic fertilizer. On the other hand, the competence of the instructor must also be adequate and understand in making liquid organic fertilizer. The purpose of this study was to determine the competency of Simantri's companion in biourine technology transfer and dissemination of biourine technology in the Simantri group in Tabanan Regency. The sample used in the study amounted to 30 respondents Data obtained in this study were processed and tabulated using quantitative analysis methods.Based on the results of research on simantri companion competencies in Tabanan Regency, it consists of (1) Mastery of biourine technology shows that the category is very high, this is supported by giving information, reaching a score of 133 which shows very high categories in the parameters of management. (2) Competencies obtained from the application process obtained in using the tools directly that reach a very high category with a total score of 120 in the usage time parameter. (3) Then the competency in disseminating biourine technology which reaches a very high category is obtained on the indicator. counseling with a score of 131 in the percentage parameters.The facilitator gave more training to the Simantri group, especially in mastering technology, the application process and also dissemination in the making of biourine, and it was hoped that the Simantri companion would give more information about biourine so that the mastery of making biourine was better.